2017
DOI: 10.3892/ol.2017.7094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipodox in combination with bevacizumab in a patient with a metastatic malignant phyllodes breast tumor: A case report

Abstract: A 76-year-old female patient with a malignant phyllodes tumor underwent modified radical mastectomy and wide excision. Multiple nodules were observed in the operated wound area. Positron emission tomography-computed tomography (PET-CT) revealed recurrent disease in the left breast, the adjacent left third rib, the left internal mammary region and the left ilium. A novel formulation of bevacizumab (5 mg/m2, first day) in combination with liposomal doxorubicin (Lipodox, 30 mg/m2, second day) was administered for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…One case study demonstrated combining neoadjuvant liposomal doxorubicin and bevacizumab allowed adequate tumor shrinkage for resection and metastasectomy. 52 A second case report demonstrated that liposomal doxorubicin in conjunction with albumin-bound paclitaxel, cisplatin, and accelerated radiotherapy led to the patient being disease-free after two years of follow-up. 53…”
Section: Methodsmentioning
confidence: 99%
“…One case study demonstrated combining neoadjuvant liposomal doxorubicin and bevacizumab allowed adequate tumor shrinkage for resection and metastasectomy. 52 A second case report demonstrated that liposomal doxorubicin in conjunction with albumin-bound paclitaxel, cisplatin, and accelerated radiotherapy led to the patient being disease-free after two years of follow-up. 53…”
Section: Methodsmentioning
confidence: 99%
“…Small series and single cases of metastatic breast phyllodes tumours published report the use of doxorubicin-based systemic chemotherapy 13–16. Liposomal doxorubicin in combination with bevacizumab has been reported in one case 17. In an Indian report, epirubicin with ifosfamide was administered to four patients 18.…”
Section: Introductionmentioning
confidence: 99%